Strategi BAZNAS dalam Mengatasi Ketimpangan Penerimaan Dana Zakat (Studi Kasus : BAZNAS Kabupaten Sanggau Kalimantan Barat) - Rahmah Yulisa Kalbarini; Muhammad Amin Zaki (UIN Mataram, 2021)
Strategy of BAZNAS to Resolve Inequality of Zakat Fund Receipts (Case Study: BAZNAS, Sanggau District, West Kalimantan) is a descriptive qualitative research that is a study that describes the facts that exist in the field in the form of text, because to capture a deep understanding not only through data in the form of number. Data collection tools are the method of observation, interviews, documentation, and library research. The purpose of this research is to find out: 1) The practice of the distribution of zakat funds to the community in Sanggau Regency 2) The solution in overcoming the inequality of the receipt of zakat funds from the community of Sanggau District. The results of the study were first, the distribution of zakat funds in the Sanggau District Baznas was distributed to the poor, poor, Ibn Sabil, amil, and reverts. This is according to Imam Shafi’i, alms must be given eight groups if any. If not, zakat is only given to existing ones. Second, zakat funds must also be distributed evenly and regularly, especially for the poor so that they can make a living. Third, increasing the effectiveness of distribution so that the funds raised can be felt by all mustahik. Based in the above research, the author can provide suggestions for increasing the collection of funds so that the distribution of zakat funds is greater. Thus there will be no imbalance in the receipt of zakat funds on mustahik.